Public awareness of childhood language impairment in Turkey: A descriptive study - Kement, Nurcan; Topbaş, Saime Seyhun; Bulut, Talat (Turkiye Klinikleri, 2022)
Objective: Childhood language impairment (CLI), also known as developmental language disorder, adversely affects children’s expressive and/or receptive language development. Although relatively significant action has been taken to raise public awareness about other developmental disorders in Turkey, limited attention has been paid to CLI. Moreover, no previous study has been conducted about awareness of the Turkish population about CLI. Material and Methods: We carried out the Turkish version of a survey developed by Working Group 3 of COST Action IS1406 to estimate public awareness of CLI regarding its nature, causes and the problems associated with it. Data were collected in the form of face-to-face interviews. The sample included 87 participants from socio-economically diverse districts of İstanbul, Turkey, determined on the basis of the Human Development Index. Results: A significantly lower number of the participants reported having heard of CLI compared to autism, attention-deficit/hyperactivity disorder and speech disorder. Another finding was that women with children reported having heard of CLI significantly more than those without children. It was also observed that the participants had inadequate knowledge of the problems that individuals with CLI have and of its causes. Conclusion: The current findings highlight the need to take more action to raise public awareness about CLI in Turkey.

Amaç: Çocukluk çağı dil bozukluğu (ÇÇDB), diğer adıyla gelişimsel dil bozukluğu, çocukların alıcı ve/veya ifade edici dil gelişimini olumsuz yönde etkilemektedir. Türkiye’de diğer gelişimsel bozukluklara ilişkin toplumsal farkındalığın artırılmasına yönelik ciddi çalışmalar yapılmış olmakla birlikte ÇÇDB’ye yönelik çalışmalar sınırlı kalmıştır. Ayrıca Türkiye’de ÇÇDB’ye ilişkin toplumsal farkındalık üzerine yapılmış bir çalışma bulunmamaktadır. Gereç ve Yöntemler: Bu çalışmada ÇÇDB’nin doğası, sebepleri ve ÇÇDB ile ilişkilendirilen sorunlara ilişkin toplumsal farkındalığı ölçmek amacıyla COST Aksiyonu IS1406 3. Çalışma Grubu tarafından geliştirilen anketin Türkçe versiyonu uygulanmıştır. Veriler yüz yüze gerçekleştirilen mülakatlar ile toplanmıştır. İstanbul’un sosyoekonomik açıdan farklı ilçelerinden 87 katılımcı örneklemi oluşturmuş olup bu ilçeler İnsani Gelişme Endeksi kullanılarak belirlenmiştir. Bulgular: Otizm, dikkat eksikliği hiperaktivite bozukluğu ve konuşma bozukluklarına kıyasla anlamlı oranda daha az katılımcı ÇÇDB terimini duyduğunu belirtmiştir. Çalışmanın bir diğer bulgusu, çocuğu olmayan kadınlara kıyasla çocuğu olan kadınlar arasında ÇÇDB teriminin daha fazla duyulmuş olmasıdır. Ayrıca çalışma örnekleminin, ÇÇDB’si olan bireylerin yaşadıkları sorunlar ve ÇÇDB’nin sebeplerine dair yetersiz bilgi sahibi olduğu gözlenmiştir. Sonuç: Çalışmanın bulguları, Türkiye’de ÇÇDB’ye ilişkin toplumsal farkındalığın artırılması için harekete geçilmesi gerektiğini göstermektedir.
Türkiye’de çocukluk çağı dil bozukluğuna ilişkin toplumsal farkındalık: Betimsel çalışma
Keywords: Childhood Language Impairment; Developmental Language Disorder; Specific Language Impairment; Public Awareness; Çocukluk Çağı Dil Bozukluğu; Gelişimsel Dil Bozukluğu; Özgül Dil Bozukluğu; Toplumsal Farkındalık